L’utilisation de pesticides fait-elle partie des stratégies d’adaptation au changement climatique ? Analyse exploratoire dans le Fossé rhénan (France-Allemagne) - Gaël Bohnert; Brice Martin (VertigO)
While the consequences of climate change are becoming more and more visible and it is not possible anymore to avoid them, pesticides use in agriculture is subject to a profound call into question due to environmental, economic and sanitary reasons. Agriculture is thus confronted with a double challenge: adapting to climate change and evolving towards less dependence on pesticides. These stakes are particularly significant in the Rhine Valley. Indeed, in this space where the consequences of climate change could be intense, traditional models with high pesticide use (intensive crop cultivation and reputed wine growing) cohabit with organic and biodynamic farming productions, mostly in wine growing. The local context could thus form an injunction to ecologically improve agricultural practices. Yet, decreasing pesticides use and adapting to climate change are sometimes contradictory objectives, even if many strategies allow reconciling both. To enlighten this paradox and understand the role of multiple borders in this cross-border space, we based on the comparison between sectors (crop cultivation and wine-growing) on the one side, and between countries (France and Germany) on the other side, to bring out the technical, regulatory, even cultural accelerators and obstacles to the implementation of these win-win strategies of a heterogeneous and rather complex agricultural transition: farmers indeed seek to reconcile different objectives, adaptation to climate change and/or its mitigation, decrease in pesticides use and preservation of biodiversity. Certainly, this is sometimes used as a commercial argument. Still, it also has to do with a real personal conviction for which social interactions play an important role: information spread by the agricultural organizations, exchanges between farmers, personal reflections and trials, and experiences abroad. The cross-border context of the Rhine Valley takes all its importance and, in spite of multiple borders, favours decision-taking facing environmental stakes.